Development of a questionnaire on nutritional knowledge for the obese hospitalized patient: the NUTRIKOB questionnaire - Mambrini, Sara Paola; Soranna, Davide; Averna, Eva; Di Guglielmo, Giulia; Lucchetti, Elisa; Tinozzi, Tiziana; Vinci, Calogero; Barbieri, Valerio; Zambon, Antonella; Bertoli, Simona; Scacchi, Massimo (Frontiers in Nutrition, 2023)
Different approaches, involving different areas and figures, are useful for the rehabilitation of obese subjects through a multidisciplinary hospital path. A focal point of rehabilitation is represented by education on healthy eating by increasing the dietary knowledge patients. Few tools investigating food knowledge are available in Italy: therefore, the need has emerged to develop easy-to-use tools for clinical practice that allow to detect food knowledge to set up a more targeted food re-education. The following work aimed at building and validating a questionnaire capable of investigating the dietary knowledge of the population affected by obesity. Methods: A pool of experts carried out a review of the literature, gathering all the information necessary to select and construct the best set of questions and the format of the final project of the questionnaire. During statistical analysis the validity, reproducibility and stability of the questionnaire were investigate in a sample of 450 subjects with obesity. Results: early analysis disclosed that 5 questions of the original questionnaire had no discriminating power. The successive validation phases were successful, confirming good content validity, stability and reproducibility over time. Conclusion: the questionnaire has all the characteristics to be considered a valid tool for investigating dietary knowledge in the obese population.2 This is a provisional file, not the final typeset articleThe psychometric tests confirmed a good internal consistency of the structure, a validity of the content, a good reproducibility and stability over time.